Income Distribution and Macroeconomic Performance in the United States - Cole, Jeffrey (IMF Working Papers; Working Paper ;, 1996)
The factors underlying the rise in U.S. income inequality since the mid-1970s are examined. The results suggest that the trend increase in income inequality has not been related to macroeconomic developments, such as income growth or import penetration, but that the income distribution is sensitive to the cycle. Important factors that do help explain the widening of the income distribution include the increased investment in technology and the decline in the minimum wage. The rise in the share of single female-headed households, the increased proportion of households headed by someone over the age of 35, and the fall in the child-dependency ratio also help explain movements in income shares.